2010
DOI: 10.1111/j.1751-1097.2010.00705.x
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acenaphthoporphyrins with Liposomes for the Photodynamic Treatment of Leishmaniasis

Abstract: Acenaphthoporphyrins are potential photosensitizers for photodynamic therapy, but their hydrophobicity limits their potential. Liposomes have been widely investigated as delivery vehicles that can transport hydrophobic drugs in biological systems. Here we study the association of acenaphthoporphyrins with liposomes made up of dimyristoyl phosphatidylcholine (DMPC), and to liposomes made up of a mixture of DMPC, cholesterol (Chol) and distearoyl phosphatidylglycerol (DSPG) in a 2:1:0.8 molar ratio to evaluate h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(20 citation statements)
references
References 47 publications
1
19
0
Order By: Relevance
“…Different porphyrin derivatives have reported PDT activities, specifically the 5,10,15,20‐tetrakis(4‐sulfanatophenyl)‐21H,23H‐porphyrin has shown photochemical efficiency and have been reported as potential for treating carcinoma . Endogenous Protoporphyrin IX (PpIX, 7) was reported as a clinically useful photosensitizer for PDT, Hexaminolevulinate, the n‐hexyl ester of ALA, (HAL, Hexvix®, Cysview®, 10) was approved in 2010 by the US FDA in the diagnosis of bladder cancer, β‐substituted systems such as ethyl and diethyl carbo‐porphyrin, benzoporphyrin and 1–5diaryl‐porohyrin have reported activity against Leishmania (leishmanial parasite) . Nowadays, intensive research is reported on the development of new structures with PDT activity.…”
Section: Introductionmentioning
confidence: 74%
“…Different porphyrin derivatives have reported PDT activities, specifically the 5,10,15,20‐tetrakis(4‐sulfanatophenyl)‐21H,23H‐porphyrin has shown photochemical efficiency and have been reported as potential for treating carcinoma . Endogenous Protoporphyrin IX (PpIX, 7) was reported as a clinically useful photosensitizer for PDT, Hexaminolevulinate, the n‐hexyl ester of ALA, (HAL, Hexvix®, Cysview®, 10) was approved in 2010 by the US FDA in the diagnosis of bladder cancer, β‐substituted systems such as ethyl and diethyl carbo‐porphyrin, benzoporphyrin and 1–5diaryl‐porohyrin have reported activity against Leishmania (leishmanial parasite) . Nowadays, intensive research is reported on the development of new structures with PDT activity.…”
Section: Introductionmentioning
confidence: 74%
“…For all these reasons, many studies have been focused on exploring different aspects of the behaviour of these carrier systems, as the involved mechanism in cell death, 269,270 or the determination of the most favourable lipidic composition for their performance. [271][272][273] Several groups have reported on PS-liposome hybrid systems for different biomedical purposes, like imaging techniques, 274 and PDT or PDI treatments of different cancerous cell lines or tumours, [275][276][277][278][279][280][281] leishmaniasis, 282,283 Candida albicans, 284 or human chronic periodontitis, 285 among others. More interestingly, liposomes that enable the formulation of more than one active component have recently attracted much attention, as they can be employed as suitable platforms to render more complex third-generation PS (Fig.…”
Section: Ps-liposome Biohybridsmentioning
confidence: 99%
“…Lash et al reported the use of alkyl-carbaporphyrin ketal derivatives ( Figure 6) for growth inhibition of Leishmania tarentolae promastigotes by reactive oxygen species generation, such as singlet oxygen and superoxide [110]. Acenaphthoporphyrin derivatives were incorporated into liposomes, due to their low hydrophilicity, thus increasing their bioavailability and photodynamic effects in vitro against axenic and intracellular amastigotes of the pathogenic Leishmania panamensis [111]. The improved solubility consequence of the incorporation of polar groups (e.g., -OH, -COOH, -OMe) to the porphyrin ring periphery tends to enhance their activity against several parasites.…”
Section: Porphyrinsmentioning
confidence: 99%